A Triple-blind, Placebo-controlled Randomized Trial of the Ilioinguinal-transversus Abdominis Plane (I-TAP) Nerve Block for Elective Cesarean Section. Issue 1 (March 2019) - Staker, J.J.; Liu, D.; Church, R.; Carlson, D.J.; Panahkhahi, M.; Lim, A.; LeCong, T.
Abstract : ( Anaesthesia . 2018;73:594–602) Moderate or severe pain after cesarean section has been reported in 7% of women. The ilioinguinal-iliohypogastric block and the transversus abdominis plane (TAP) block have both been effective at reducing postoperative opioid requirements after lower abdominal surgery. However, in studies that compared either of these blocks with spinal morphine, there was no benefit found with the nerve blocks. Regardless, some patients do develop postcesarean pain despite receiving spinal morphine. At the investigators' institution they began performing a combined ilioinguinal-transversus abdominis plane (I-TAP) nerve block and found it provided improved analgesia. Therefore, this prospective, randomized, placebo-controlled trial was performed to formally evaluate the efficacy of the I-TAP block, hypothesizing that the addition of the block to a multimodal analgesic regimen that included spinal morphine would reduce opioid consumption in the first 24 hours after cesarean section.